2011
DOI: 10.1073/pnas.1010453108
|View full text |Cite
|
Sign up to set email alerts
|

Double-lock ratchet mechanism revealing the role of αSER-344 in F o F 1 ATP synthase

Abstract: In a majority of living organisms, F o F 1 ATP synthase performs the fundamental process of ATP synthesis. Despite the simple net reaction formula, ADP þ P i → ATP þ H 2 O, the detailed step-by-step mechanism of the reaction yet remains to be resolved owing to the complexity of this multisubunit enzyme. Based on quantum mechanical computations using recent high resolution X-ray structures, we propose that during ATP synthesis the enzyme first prepares the inorganic phosphate for the γP-O ADP bond-forming step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…We and others have earlier shown that αSer344 in the α 341 NVISIT 346 helix plays an important role in the preparation of the transition state (TS) (15,31). Our QM results have also suggested that the side chain of αS344 has to turn to the active site and form a hydrogen bond with O=γP of ATP (15). This flipping of the Ser side chain can be observed in the MD simulation in T* after ∼9.7 ns (Fig.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…We and others have earlier shown that αSer344 in the α 341 NVISIT 346 helix plays an important role in the preparation of the transition state (TS) (15,31). Our QM results have also suggested that the side chain of αS344 has to turn to the active site and form a hydrogen bond with O=γP of ATP (15). This flipping of the Ser side chain can be observed in the MD simulation in T* after ∼9.7 ns (Fig.…”
Section: Resultssupporting
confidence: 49%
“…According to single-molecule experiments, the bond-breaking step takes place after an ∼90°rotation of the γ-subunit, thus in between the two conformations, most likely in a near-D structure (12). This conclusion was supported by theoretical studies (13,15,16), and recently, we provided indications that the barrier height for the hydrolysis step decreases significantly when the active site conformation changes from T to D (15,16). Additional support was obtained from single-molecule manipulations (17).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Obviously, this is still a work in progress ; however, it also illustrates the need for careful experimental and theoretical analyses of this problem. In this respect, it may be useful to expand here on current QM/MM studies of ATP hydrolysis in proteins and in solution (Akola & Jones, 2006 ;Beke-Somfai et al 2011 ;Dittrich et al 2003 ;Grigorenko et al 2007b ;Li & Cui, 2004), some of which have not attempted to obtain quantitative results (e.g., Dittrich et al 2003), and others of which have major problems due to not having included a sufficiently large part of the environment, and in having no sampling. In fact, the difficulties of reproducing the observed barrier led to the problematic message that has emerged from the work of (Grigorenko et al 2007b).…”
Section: The Energetics Of the Chemical Stepmentioning
confidence: 99%